The Struggle for Recognition of Local Beliefs in Indonesia: 100 Years of Pran Soeh's Mindfulness Strategy - Dian Nur Anna; Maryono Maryono; Muhammad Wakhid Musthofa (Endogami: Jurnal Ilmiah Kajian Antropologi, 2026)
Over the past century, Indonesia’s shifting political regimes have constrained local belief communities, including Pran Soeh from Muntilan, Central Java. This article analyzes Pran Soeh’s century-long pursuit of formal state recognition, a struggle intensified after 1965 when several members were accused of links to the G30S/PKI—an enduring stigma that undermined social legitimacy. Drawing on qualitative ethnography, we conducted participant observation, in-depth interviews, and historical and administrative document analysis. Data were analyzed using Spradley’s ethnographic sequence (domain, taxonomic, componential, and cultural-theme analyses). We find that Pran Soeh repeatedly chooses non-confrontational, mindfulness-informed strategies: rejecting violence, cultivating nonjudgmental attitudes, and adopting contemplative practices that frame uncontrollable events within the moral order of nature and God. These dispositions function as an ethical-political repertoire that sustains internal cohesion, enables dialogue and legal navigation, and supports gradual recognition as a local belief. The study contributes to scholarship on religion and social movements by showing how Javanese spirituality is translated into peaceful political agency and by extending mindfulness from individual practice to socio-political resistance. We recommend affirmative state policies that strengthen inclusiveness toward local beliefs.